Understanding the contribution of developmentally distinct neutrophils to the developing haemato-immune system - Park, Y (2023)
Neutrophils play a critical role in host defense, especially in neonates whose immune systems are not yet fully developed. Neutrophils originate from at least two origins: yolk sac-derived erythromyeloid progenitors (EMPs) and aorta-derived hematopoietic stem cells (HSCs). In zebrafish, developmentally discrete neutrophil populations are associated with different functions. In addition, our transcriptomic analysis of neutrophils isolated from E18.5 fetuses has inferred three mature, yet functionally distinct, subsets, with gene set enrichment analysis indicating conventional, anti-viral and regulatory functions respectively among bone marrow neutrophils, leading us to hypothesize that mammalian neutrophils from distinct developmental origins may also have discrete functions and/or gestational stage-specific contributions to the hematopoietic system.